Caracterização antigênica de cepas de Moraxella bovis, Moraxella bovoculi e Moraxella ovis com potencial uso vacinal - Kowalski, Ananda Paula (2016)
Infectious bovine keratoconjunctivitis (IBK) is the main ocular disease of cattle. Highly contagious, it is responsible for significant economic losses of livestock worldwide. Moraxella bovis is recognized as the primary agent of the disease in cattle. However, the occurrence of other similar species, including M. ovis and M. bovoculi, recently described, have been common in outbreaks of the disease and are suspected to be causally related to the limited success of preventive measures, especially the use of bacterins containing only strains of M. bovis. This dissertation describes the antigenic characterization of M. bovis, M. bovoculi and M. ovis strains and a commercial vaccine by cross-reactivity using flow cytometry analysis and identification of immunodominant conserved antigens by Western blotting. Antisera against strains of the three species were obtained from immunization of New Zealand rabbits and challenged before a panel of strains isolated from cattle and sheep clinically affected by the disease between 1983 and 2013 as well as reference strains of each species. Field strains of M. bovoculi (Mbv2 and Mbv3) recognized satisfactorily all heterologous strains. However, Mbv3 (M. bovoculi), Mov2 (M. ovis) and Mov3 (M. ovis) strains stood out as the most intense recognition strains of their respective species and suggest that species-specific antigens play an important role in the host immune response. The association of reactivity percentage with the antigenic profiles, evidenced by Western blotting analysis, indicates that the immune response induced by Moraxella spp. appears to be mediated by multiple surface antigens of which many are shared between the three species. Among 32 different proteins identified, 22 (68.7%) were recognized by at least one antiserum in the protein extracts of all strains analyzed by Western blotting. Our study suggests (1) the selection and combination of M. bovis, M. bovoculi and M. ovis strains to be used in the composition of antigenic unit vaccines as IBK control strategy and (2) the use of flow cytometry as the most appropriate methodology for this selection.